Hubungan Tingkat Kebersihan Gigi dan Mulut dengan Karies pada Nelayan di Pesisir Pantai Watu Ulo Kabupaten Jember - Yona Anindita; Kiswaluyo Kiswaluyo; Ari Tri Wanodyo Handayani (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Activity to cleanse and refresh the teeth and mouth is oral hygiene. Caries and periodontal disease will occure if not treating well, so they need to do the treatment to maintain the oral health. Fishermen usually sail in the afternoon and return in the next morning, sometimes they stay in the sea for a day. This situation causes the lack of attention of oral hygiene and increases the occurrence of dental caries. Researcher interests to analyze the relationship of oral hygiene levels with the caries of fishermen at Dusun Watu Ulo, Sumberejo Village, Jember District, East Java. This study performs oral hygiene examination using OHI-S index and caries examination using DMF-T index. This study aimed to determine the relationship between the level of oral hygiene with caries in fishermen at the coast of Watu Ulo Beach, Jember District.This observational analytic research was conducted by cross sectional approach. The method for sampling used Cluster Sampling. he average score of OHI-S fishermen at Watu Ulo coastal Jember District was 3.90 (bad category) and the average DMF-T index score was 3.10 (medium category). There was a weak relationship between oral hygiene with caries. Keywords: Oral hygiene, Caries, OHI-S, DMF-T, Fishermen.